2014
DOI: 10.1016/j.bbadis.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

De novo GLI3 mutation in esophageal atresia: Reproducing the phenotypic spectrum of Gli3 defects in murine models

Abstract: Esophageal atresia is a common and life-threatening birth defect with a poorly understood etiology. In this study, we analyzed the sequence variants of coding regions for a set of esophageal atresia-related genes including MYCN, SOX2, CHD7, GLI3, FGFR2 and PTEN for mutations using PCR-based target enrichment and next-generation sequencing in 27 patients with esophageal atresia. Genomic copy number variation analysis was performed using Affymetrix SNP 6.0. We found a de novo heterozygous mutation in the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, neither a literature review nor the reviews of 174 GCPS/PHS patients, provided by Johnston et al (19,20), revealed the presence of our GLI3 splice variant or EA/TEF in these patients. Yet, Yang et al (21) reported a de novo missense GLI3 variant (p.M111T) in a patient with EA with hemivertebrae, resembling the phenotypic spectrum in murine models as reported by Motoyama et al (10).…”
Section: Discussionmentioning
confidence: 64%
“…However, neither a literature review nor the reviews of 174 GCPS/PHS patients, provided by Johnston et al (19,20), revealed the presence of our GLI3 splice variant or EA/TEF in these patients. Yet, Yang et al (21) reported a de novo missense GLI3 variant (p.M111T) in a patient with EA with hemivertebrae, resembling the phenotypic spectrum in murine models as reported by Motoyama et al (10).…”
Section: Discussionmentioning
confidence: 64%
“…More data would be necessary to determine if EA/TEF could be a minor feature of these syndromes. A GLI3 mutation has already been reported in a patient with EA [Yang L et al, 2014]. However, the variant found in the patient from this cohort appeared to be a non-deleterious polymorphism present in 0.6% of the European population (ExAC; http://exac.broadinstitute.org), even though it was previously thought to be associated with Greig cephalopolydactyly [Kalff-Suske et al, 1999;Krauss et al, 2009].…”
Section: Diagnoses In This Cohortmentioning
confidence: 59%
“…Likewise, the incidence of chromosome anomalies is increased in EA, with an incidence of 6 to 10 % for whole chromosome aneuploidy and an additional 1 to 2 % for copy number variants [17]. Single gene deletions, such as SHH and GLI3 , have previously been implicated in animal models of EA, and more recently reported in human cases [1820]. Therefore, it is appropriate to offer prenatal diagnosis, which aids in the management of pregnancy and informs postnatal care of the neonate.…”
Section: Discussionmentioning
confidence: 99%